PREVENTIVE MEASURES IN IMPLEMENTING PROTECTIVE MEASURES TO PREVENT CRIME (The Conference Hub, 2025)
The implementation of preventive measures in the prevention of crime has a significant impact on maintaining order in society and reducing crime. Preventive measures include raising public awareness, increasing legal knowledge, and developing anti-crime approaches. Crime can be prevented through education, various social programs, and cooperation between law enforcement agencies. The effectiveness of this process enhances the role of society in ensuring security and strengthens social stability.